Limonene inhibits Candida albicans growth by inducing apoptosis - Thakre, Archana; Zore, Gajanan; Kodgire, Santosh; Kazi, Rubina; Mulange, Shradha; Patil, Rajendra; Shelar, Amruta; Santhakumari, Bayitigeri; Kulkarni, Mahesh J.; Kharat, Kiran; Karuppayil, Sankunny Mohan (Medical Mycology, 2018)
Anti-Candida potential of limonene was evaluated against planktonic growth, biofilm (adhesion, development and maturation) and morphogenesis of Candida albicans in this study. Limonene is a major constituent of citrus oil and most frequently used terpene in food and beverage industry due to its pleasant fragrance, nontoxic, and is generally recognized as safe (GRAS) flavoring agent as well as treatment option in many gastrointestinal diseases. Limonene exhibited excellent anti-Candida activity and was equally effective against planktonic growth of C. albicans isolates differentially susceptible to FLC (N = 35). Limonene inhibited morphogenesis significantly at low concentration. However, it showed stage dependent activity against biofilm formation, that is, it was more effective against adhesion followed by development and maturation. Limonene also exhibited excellent synergy with FLC against planktonic and biofilm growth. SWATH-MS analysis led to identification of limonene responsive proteins that provided molecular insight of its anti-Candida activity. Proteomic analysis revealed upregulation of proteins involved in cell wall glucan synthesis (Kre6); oxidative stress (Rhr2, Adh7 and Ebp1); DNA damage stress (Mbf1 and Npl3); nucleolar stress (Rpl11, Rpl7, Rpl29, Rpl15) and down regulation of cytoskeleton organization (Crn1, Pin3, Cct8, Rbl2), and so forth, in response to limonene. Limonene mediated down regulation of Tps3 indicates activation of caspase (CaMca1) and induction of apoptosis in C. albicans. These results suggest that limonene inhibits C. albicans growth by cell wall/membrane damage induced oxidative stress that leads to DNA damage resulting into modulation of cell cycle and induction of apoptosis through nucleolar stress and metacaspase dependent pathway.